2009
DOI: 10.1111/j.1550-7408.2009.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Theileria gilberti n. sp. (Apicomplexa: Theileriidae) in the Gilbert's Potoroo (Potorous gilbertii)

Abstract: The morphology and genetic characterisation of a new species of piroplasm identified in the blood of the Gilbert's potoroo (Potorous gilbertii) from the Two Peoples Bay Nature Reserve near Albany, Western Australia, is described from blood and tissue samples from 16 Gilbert's potoroos. Microscopy of blood showed these parasites are highly pleomorphic with a mean length of 1.8 mum and mean width of 0.85 mum. Phylogenetic analysis of 18S rRNA sequence data identified the piroplasm as a new species of Theileria t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…(Lee et al 2009). An earlier study by Cox (1977) showed that piroplasms enhance and prolong trypanosome infections particularly in stercorarian-transmitted trypanosomes and generally occur together in the wild.…”
Section: Infection and Pathogenesismentioning
confidence: 99%
“…(Lee et al 2009). An earlier study by Cox (1977) showed that piroplasms enhance and prolong trypanosome infections particularly in stercorarian-transmitted trypanosomes and generally occur together in the wild.…”
Section: Infection and Pathogenesismentioning
confidence: 99%
“…in Australian monotreme and marsupial hosts is relatively high; Collins et al (1986) found 53/54 (98%) platypuses trapped in New South Wales were infected with T. tachyglossi and a similar prevalence, 16/16 (100%), was reported for T. gilberti in Gilbert's potoroos in Western Australia (Lee et al, 2009). In our study, like that of Lee et al (2009), we also utilized PCR analysis to detect piroplasm infection rates; this method confirmed the high prevalence of infection in all but the Warrup site (Table 1) and although only a subset of samples were screened by microscopy (32/153), all the microscopy positives corresponded with the PCR positives. The results of the present study suggest that the parasite is widespread among woylies and can probably be considered to be endemic in this host species in these localities in Western Australia.…”
Section: Discussionmentioning
confidence: 75%
“…Although little is known about the clinical effects of piroplasm infections in marsupials, high parasitaemias appear to be well tolerated in some species (e.g. the Gilbert's potoroo, Potorous gilbertii) and have little pathological effect (Lee et al, 2009), yet in others, such as the agile antechinus (Antechinus agilis), babesiosis has been reported as a cause of anaemia in moribund males undergoing semelparity ( Cheal et al, 1976 andBarker et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations